Cancer registries - guardians of breast cancer biomarker information: A systematic review. Issue 2 (June 2019) - Voith von Voithenberg, Lena; Crocetti, Emanuele; Martos, Carmen; Dimitrova, Nadya; Giusti, Francesco; Randi, Giorgia; Rooney, Roisin; Dyba, Tadeusz; Bettio, Manola; Negrão Carvalho, Raquel
Background: Breast cancer is the most common cancer and the leading cause of cancer-related death in females, with a large societal and economic impact. Decisions regarding its treatment are largely affected by the categorization into different subtypes with hormone receptor status and HER2 status being the most important predictive factors. Other biological markers play an important role for prognostic and predictive reasons. The data collection and harmonization of cancer cases are performed by cancer registries whose collection of parameters largely differs, partially including results from biomarker testing. Methods: This systematic literature review consisting of a total of 729 reports determined whether information about biomarker testing in breast cancer cases is collected and published by cancer registries worldwide. Results: The number of publications using breast cancer biomarker data from registries steeply rose with the beginning of the 21st century and some hospital-based and population-based cancer registries reacted with immediate collection of biomarker data following the recommendation of clinical guidelines. For female breast cancer, biomarkers have achieved an essential clinical value and this review points to a steady increase in the collection of biomarker data by cancer registries during the last decade. Conclusions: In the future, recommendations for biomarker data collection and coding by cancer registries may be required to ensure harmonization and comparability of the data.